(5RS)‐6H‐Spiro[pyrazolo[1, 5‐c]quinazoline‐5, 4′‐thiochroman]: efficient synthesis under mild conditions, molecular structure and supramolecular assembly. Issue 11 (1st November 2015) - Quiroga, Jairo; Gálvez, Jaime; Cobo, Justo; Glidewell, Christopher
Abstract : Pyrazolo[1, 5‐ c ]quinazolines are fused‐quinazoline derivatives which have been reported as potential agents against neurological disorders. The normal synthesis routes to these compounds require harsh reaction conditions, long reaction times or multistep sequences. The title compound, C18 H15 N3 S, has been prepared under very mild conditions by condensation of thiochroman‐4‐one with 5‐(2‐aminophenyl)‐1 H ‐pyrazole, which had itself been prepared by the reaction of hydrazine hydrate with 4‐hydroxyquinoline mediated by a brief period of microwave heating. Within the molecule in the crystal structure, the reduced pyrimidine ring adopts an envelope conformation, whereas the thiane ring adopts a half‐chair conformation. Molecules are linked into sheets by a combination of one N—H...S hydrogen bond and two independent C—H...π(arene) hydrogen bonds, which utilize the same aryl ring as the acceptor, with one C—H bond donating to each face of the ring. Comparisons are made with some related compounds.